Morphometric and Morphological Analysis of Trindade Island, South Atlantic, Brazil - Nogueira, Gabriel; Frederica Effgen, Julia; Marchioro, Eberval (Sociedade & Natureza, 2020)
Although being well established in continental watersheds, morphometric analysis is still incipient in oceanic islands. This paper aims to analyze the morphometry and morphologically classify the Trindade Isle, in South Atlantic. The parameters used were altitude, slope gradient, LS factor, Topographic Wetness Index (WTI) and Geomorphons classification. Trindade isle has an altimetric amplitude of 600m, with 34% of its area between 0-100m and 21.2% in the 100-200m class. The isle’s lower parts are gravel and sand beaches and alluvial fans. Ridgelines such as the Desejado and Verde peaks represent heights above 500m and occupy 2% of the isle’s area. Slope gradients vary from strongly undulated (20-45%) to hilly (45-75%), with both classes occupying half the isle’s area. Flatter areas (with slope gradients between 0-3% and 3-8%) occupy less than 4% of the isle. The slope faces more exposed to weather conditions (rainfall and winds) are the oriented to east and southeast, therefore being the most prone to modelling relief processes. The western and northwestern faces are steeper and more sheltered. The Geomorphons classification has shown that 57% of the isle is composed by straight slopes, 19% are spurs (slightly convex slopes in plan and profile), and 18.6% are hollows. The WTI shows that the areas prone to saturation are relief concavities and in the medium to lower thirds of the slopes.